Inflammatory pathways in alcoholic steatohepatitis - Gao, Bin; Ahmad, Maleeha F.; Nagy, Laura E.; Tsukamoto, Hidekazu (Journal of hepatology, 2019)
Inflammatory processes are primary contributors to the development and progression of alcoholic steatohepatitis (ASH), with severe alcoholic hepatitis characterised by non-resolving inflammation. Inflammation in the progression of ASH is a complex response to microbial dysbiosis, loss of barrier integrity in the intestine, hepatocellular stress and death, as well as inter-organ crosstalk. Herein, we review the roles of multiple cell types that are involved in inflammation in ASH, including resident macrophages and infiltrating monocytes, as well as other cell types in the innate and adaptive immune system. In response to chronic, heavy alcohol exposure, hepatocytes themselves also contribute to the inflammatory process; hepatocytes express a large number of chemokines and inflammatory mediators and can also release damage-associated molecular patterns during injury and death. These cellular responses are mediated and accompanied by changes in the expression of pro- and anti-inflammatory cytokines and chemokines, as well as by signals which orchestrate the recruitment of immune cells and activation of the inflammatory process. Additional mechanisms for cell-cell and inter-organ communication in ASH are also reviewed, including the roles of extracellular vesicles and microRNAs, as well as inter-organ crosstalk. We highlight the concept that inflammation also plays an important role in promoting liver repair and controlling bacterial infection. Understanding the complex regulatory processes that are disrupted during the progression of ASH will likely lead to better targeted strategies for therapeutic interventions.